2019
DOI: 10.2174/1573412914666180710114458
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Analysis of Antipsychotics

Abstract: Introduction: Schizophrenia is seizures accompanied by severe psychotic symptoms, and a steady state of continuation in the form of periods of stagnation. Antipsychotics are now the basis of treatment for schizophrenia and there is no other molecule that is antipsychotic priority in treatment. Antipsychotics can be classified into two groups; dopamine receptor antagonists such as promazine, fluphenazine etc. and serotonin-dopamine antagonists including risperidone, olanzapine, ziprasidone, aripiprazole etc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…The requirement for fluorescent labeling and the inability to perform dynamic analysis are disadvantages for QDs‐based fluorescent biosensors. Moreover, QDs have low stability, easy aggregation, and difficult to control size of the particles (Karadurmus et al., 2021). To overcome these disadvantages, combining QDs with other nanomaterials is an intriguing option.…”
Section: Incorporation Of Nanomaterials Into Biosensor For Signal Amp...mentioning
confidence: 99%
“…The requirement for fluorescent labeling and the inability to perform dynamic analysis are disadvantages for QDs‐based fluorescent biosensors. Moreover, QDs have low stability, easy aggregation, and difficult to control size of the particles (Karadurmus et al., 2021). To overcome these disadvantages, combining QDs with other nanomaterials is an intriguing option.…”
Section: Incorporation Of Nanomaterials Into Biosensor For Signal Amp...mentioning
confidence: 99%
“…These medications, often called psychotropic drugs, affect the way in which receptors, transporters, and enzymes function in the body. 34 Electrochemical sensors have been developed for 35 antipsychotics, [36][37][38][39][40][41][42] anti-anxiety medications, 35 antidepressants [43][44][45][46][47][48][49][50] and the mood stabilizer lithium. 51 However, electrochemical detection can be difficult because without sample preparation, there are often interfering signals.…”
Section: Electrochemical Detection Of Psychiatric Medicationsmentioning
confidence: 99%
“…52 There are a number of different antipsychotics; their electroactive nature enables their detection, which has been extensively reviewed. 42 In a recent example, a glassy carbon electrode modified with tannic acid and carbon nanotubes was used to detect the common antipsychotic clozapine. Their sensor had a limit of detection of 0.55 nM, a linear range of 55 nM-375 nM and was functional in serum and urine samples.…”
Section: Electrochemical Detection Of Psychiatric Medicationsmentioning
confidence: 99%
“…There are also electroanalytical techniques such as potentiometry (Rouhani & Soleymanpour, 2019), amperometry with HPLC (Raggi et al, 2000), and voltammetry. Voltammetric methods are used for the determination of many antipsychotics including olanzapine (Karadurmus et al, 2019;Kul, 2019), the oxidative behavior of olanzapine with modified electrodes (Azab & Amany, 2019;Behzad et al, 2016;Ahmed et al, 2015;Shahrokhian et al, 2014;El Shal, 2013;Mashhadizadeh & Afshar, 2012;Merli et al, 2012), and the oxidative behavior of olanzapine on a glassy carbon electrode (Yılmaz et al, 2017;Biryol & Erk, 2013). However, an electroreduction study of olanzapine has not yet been reported.…”
Section: ___________________mentioning
confidence: 99%